POTENSI TAPE SEBAGAI PANGANAN TRADISIONAL TERHADAP EFEK HEPATOTOKSIK TIKUS TERINDUKSI KARBON-TETRAKLORIDA - Gidion Krisnadi Yoseph; Christiana Destia Anggraeni; Ni Luh Putu Dian Prawita Putri; Phebe Hendra (Universitas Sanata Dharma, 2016)
Abstract: The purpose of this study was to determine the effect of "Tape" that has an alcoholic compound, to the hepatotoxic effect in the rat induced Carbon Tetrachloride. And also determine which fermentation time of the Tape can give effect to the hepatotoxic in the rat induced Carbon tetrachloride. Healthy rats were randomly divided into 7 groups of 5 animals in each. Group 1 received carbon tetrachloride 2ml/kgBW treated intraperitoneal. Group 2-4 were given "Tape" suspension 18g/kgBW once daily for 6 days with different fermentation time (3, 5, 7 days). Group 5-7 were given "Tape" suspension 18g/KgBW once daily for 6 days with different fermentation time and carbon tetrachloride was given on the 7th day. Blood sample from all groups was obtained by sinus orbitalis after 24 hours application for estimation the serum level of transaminase. The result showed that "Tape" suspension had a potential effect to reduce the hepatotoxicity induced by carbon tetrachloride. "Tape" suspension with 5 days fermentation was significantly decreased serum level of transaminase (P<0,05) upon carbon tetrachlorideinduced hepatic damage in rats. Keywords: hepatotoxicity, tape, fermentation time,carbon tetrachloride